Wall Shear Stress-Based Hemodynamic Descriptors in the ‎Abdominal Aorta Bifurcation: Analysis of a Case Study - A. Soares (Isfahan University of Technology, 2021)
The knowledge of hemodynamic behaviour in the abdominal aorta artery bifurcation is of great ‎importance for the early diagnosis of several cardiovascular diseases common in this bifurcation. The ‎work developed focuses on a case study of hemodynamic in the abdominal aorta artery bifurcation, ‎based on a realistic 3D geometric model reconstructed from 2D medical images of a real patient. ‎Hemodynamic quantities based on the wall shear stress (WSS) of the abdominal aorta bifurcation are ‎analysed and is presented an alternative analysis of the well-established stress hemodynamic descriptors ‎to identify specific zones of the artery with a higher probability of developing cardiovascular diseases. ‎The individual analysis of different zones of the artery allowed to obtain information that can remain ‎masked when whole artery is considered as a single zone. The reported results provide a correlation ‎between the analysed stress hemodynamic descriptors and the area of the wall artery. Then, the aim of ‎this work is the identification of regions at the luminal surface subject to atherosusceptible WSS ‎phenotypes. For the patient studied, the analysis presented allowed the identification of the patient's ‎propensity to develop atherosclerosis, according to the hemodynamic descriptors time-averaged WSS ‎‎(TAWSS), oscillatory shear index (OSI), and relative residence time (RRT). Thus, this work offers a new ‎way of looking to the stress hemodynamic descriptors.‎